ВАЖНОСТЬ ВЛИЯНИЯ ТЕПЛОВОЙ СРЕДЫ В ЗЕРНОХРАНИЛИЩАХ - Холмуродова З.Д. (Journal of new century innovations, 2024)
Annotation: A review of the current state of theoretical and experimental research in the field of spontaneous combustion of plant raw materials taking into account the vital activity of microflora in silos of the elevator is shown, the urgency of the issue and the necessity of calculating safe conditions for long-term grain storage are shown.